High-performance Sb2S3 photoanode enabling iodide oxidation reaction for unbiased photoelectrochemical solar fuel production. Issue 11 (6th October 2022) - Park, Young Sun; Jin, Xiaoyan; Tan, Jeiwan; Lee, Hyungsoo; Yun, Juwon; Ma, Sunihl; Jang, Gyumin; Kim, Taehoon; Shim, Sang Gi; Kim, Kyungmin; Lee, Jeongyoub; Lee, Chan Uk; et al.
Abstract : The Sb2 S3 -based photoanode is combined with a silicon photocathode for implementing a bias-free photoelectrochemical tandem device driving hydrogen evolution reaction coupled with IOR, affording operation current density of 4 mA cm −2 . Abstract : The traditional photoelectrochemical (PEC) tandem configuration of hydrogen evolution reaction and oxygen evolution reaction (OER) demands a considerable potential of 1.8 V due to theoretical water splitting potential as well as a large overpotential mainly derived by sluggish OER kinetics. The iodide oxidation reaction (IOR) is a promising alternative to OER due to its low thermodynamic energy and two-electron-involved fast reaction kinetics. Herein, we report a high-performance catalyst-modified Sb2 S3 photoanode to drive IOR. A compact thin-film-type Sb2 S3 absorber is fabricated via solution processing based on a thorough understanding of the molecular interaction in the precursor ink state. Moreover, the deposition of a multilayered catalyst RuO2 nanosheet and polydiallyldimethylammonium chloride not only efficiently enhances the charge transfer kinetics but also passivates the surface defects of the Sb2 S3 absorber. The resulting photoanode exhibits an efficient photocurrent density of 10 mA cm −2 at 0.54 V compared to the normalized hydrogen electrode in hydroiodic acid. In conclusion, we demonstrate a bias-free PEC tandem device based on a RuO2 -modified Sb2 S3 photoanode paired with a silicon photocathode, yielding an operation current density of 4 mA cm −2 .